Chamber music in England, l675-l720 - Tilmouth, Michael (s.n.], 1959)
Vol. I. Discussion of musical life in England, 1675-1720 and lists of chamber music -- Vol. II. Transcriptions of 48 musical examples mentioned in Vol. I.